A grim return: post-deportation risks in Uganda - Onyoin, C (Refugee Studies Centre, University of Oxford, 2017)
Neither the UK nor Uganda monitors what happens during and after deportation by the UK of failed Ugandan asylum seekers, despite evidence of violence and grave abuses of individuals’ human rights.